2021
DOI: 10.18335/region.v8i2.339
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Self-Medication and Antibiotic Resistance: Multilevel Regression Analysis of Repeat Cross-Sectional Survey Data in Europe

Abstract: Antibiotic resistance is a global public health issue with several anthropogenic drivers, including antibiotic consumption. Recent studies have highlighted that the relationship between antibiotic consumption and antibiotic resistance is contextualised by a variety of socioeconomic, cultural, and governance-related drivers of consumption behaviour and contagion that have been underexamined. A potential complication for research and policy is that measures of antibiotic consumption are often reliant on prescrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…The second part of the special issue includes four papers that discuss regional and spatial aspects of the healthcare sector more broadly. Two of them investigate the impact of public investments (Vadia, Blankart 2021, Fidrmuc et al 2022, one analyses antibiotic self-medication (Anderson 2021) and one the effects of Malaria on the height distribution in Italy (Percoco 2021). Vadia, Blankart (2021) investigate the role of public funding in cardiovascular device innovation.…”
Section: Contents Of This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The second part of the special issue includes four papers that discuss regional and spatial aspects of the healthcare sector more broadly. Two of them investigate the impact of public investments (Vadia, Blankart 2021, Fidrmuc et al 2022, one analyses antibiotic self-medication (Anderson 2021) and one the effects of Malaria on the height distribution in Italy (Percoco 2021). Vadia, Blankart (2021) investigate the role of public funding in cardiovascular device innovation.…”
Section: Contents Of This Special Issuementioning
confidence: 99%
“…Results indicate that the injection of EU funds is associated with a significant but small decrease in the readmission rate in the following year, but not with a change in mortality. Anderson (2021) considers drivers and consequences of antibiotic self-medication in Europe using extensive survey data from the Eurobarometer. The author explores the individual-level and national-contextual determinants of self-medication among antibiotic consumers in European countries.…”
Section: Contents Of This Special Issuementioning
confidence: 99%
“…Recent studies have documented the determinants of non-prescription antibiotic use across low-, middle-, and high-income countries and found that patient-level (sociocultural and sociodemographic) factors and healthcare system barriers contribute to non-prescription antibiotic use [ 7 , 8 , 9 ]. In the United States (US), Hispanic communities have one of the highest reported prevalence rates of non-prescription antibiotic use, with the prevalence ranging from 19 to 66% [ 9 ].…”
Section: Introductionmentioning
confidence: 99%